A PENGEMBANGAN MEDIA PEMBELAJARAN DASAR-DASAR OTOMOTIF SUB POKOK SISTEM REM BERBASIS TRAINER: PENGEMBANGAN MEDIA PEMBELAJARAN DASAR-DASAR OTOMOTIF SUB POKOK SISTEM REM BERBASIS TRAINER - I Made Satrya Adi Wibawa; Edi Elisa; Gede Widayana; Kadek Rihendra Dantes (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
This study aims to develop a trainer-based learning medium for the brake system topic, determine the medium's feasibility, and assess its practicality. The study was motivated by the limited availability of practical learning media to assist students in understanding brake system concepts within the Automotive Fundamentals course at the Mechanical Engineering Education Study Program, Universitas Pendidikan Ganesha. The study employed the Research and Development (R&D) method using the 4D development model (Define, Design, Develop, and Disseminate); however, the research was conducted only up to the Develop stage. The research subjects consisted of two design experts, two manufacturing experts, 15 students for the small-group trial, and 30 students for the large-group trial. Data were collected via questionnaires and analyzed using quantitative descriptive analysis. The results indicated that the instrument's content validity score was 0.926, falling into the "very high" category. Validation results showed scores of 91.81% from design experts and 91.25% from manufacturing experts, classifying the learning medium as "highly feasible." Practicality test results yielded scores of 85.80% for the small group and 89.90% for the large group, placing the medium in the "highly practical" category. Thus, the trainer-based learning medium for the brake system topic is deemed valid, highly feasible, and highly practical for use in the Automotive Fundamentals course. Keywords: learning medium, trainer, brake system, automotive fundamentals, research and development.